Protection of schoolchildren in risk groups against smoking and their social education - Levano-Francia, Luz (2021)
In the educational context, it is up to educators to offer schoolchildren different ways to prevent tobacco use, an action that is undertaken through interaction and support with the family and the community. The purpose of this article is to carry out a study on the protection of schoolchildren in risk groups against smoking and their social education.